2023
DOI: 10.1111/imb.12844
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing provides insights into the evolution of gene families encoding plant cell wall‐degrading enzymes in longhorned beetles

Abstract: With more than 36,000 species, the longhorned beetles (family Cerambycidae) are a mega‐diverse lineage of mostly xylophagous insects, all of which are represented by the sole sequenced genome of the Asian longhorned beetle (Anoplophora glabripennis; Lamiinae). Their successful radiation has been linked to their ability to degrade plant cell wall components using a range of so‐called plant cell wall‐degrading enzymes (PCWDEs). Our previous analysis of larval gut transcriptomes demonstrated that cerambycid beetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…Surveying the larval gut transcriptome of the Lamiinae E. adspersus (Shin et al, 2021), we initially identified a transcript with a 1347 bp-long ORF encoding a protein of 448 amino acids sharing up to 69% sequence identity with fungal glycoside hydrolase family 7 (GH7) proteins. We found the corresponding gene located on a 130-kb contig (Genbank accession: JANEYG010000319.1) of a draft genome of the same species (Shin et al, 2023). The only other gene present on this contig encoded another GH7 protein, and both genes were surrounded by insectlike transposable elements.…”
Section: The Genome Of E Adspersus Harbors Two Gh7 Genesmentioning
confidence: 94%
See 3 more Smart Citations
“…Surveying the larval gut transcriptome of the Lamiinae E. adspersus (Shin et al, 2021), we initially identified a transcript with a 1347 bp-long ORF encoding a protein of 448 amino acids sharing up to 69% sequence identity with fungal glycoside hydrolase family 7 (GH7) proteins. We found the corresponding gene located on a 130-kb contig (Genbank accession: JANEYG010000319.1) of a draft genome of the same species (Shin et al, 2023). The only other gene present on this contig encoded another GH7 protein, and both genes were surrounded by insectlike transposable elements.…”
Section: The Genome Of E Adspersus Harbors Two Gh7 Genesmentioning
confidence: 94%
“…The GH7-encoding gene sequence was obtained from two sources: a larval midgut transcriptome of E. adspersus (Shin et al, 2021), and the draft genome of the same species (Shin et al, 2023). The sequences were manually curated and submitted to NCBI (accessions: OQ721898 and OQ721899).…”
Section: Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many instances of glycoside hydrolase genes being incorporated into the genomes of insects, fungi, and plants via HGT (Acuña et al, 2012; Da Lage et al, 2013; Kfoury et al, 2024; Kirsch et al, 2014; Pauchet and Heckel, 2013; Shelomi et al, 2014; Shen et al, 2003; Shin et al, 2023; Wheeler et al, 2013; Wybouw et al, 2016). In this study, we characterize an HGT event of a gene encoding for a glycoside hydrolase family 26 (GH26) protein, which are enzymes that break down carbohydrates present in plant cell walls, specifically mannans and galactomannans (Braithwaite et al, 1995; Gao et al, 2023; Patel et al, 2016; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%